A Quasi Experimental Study to assess the Effectiveness of Administration of Pomegranate Arils on Elevation of Hemoglobin Level among Adolescent Girls Staying in Selected Hostel - Ugle, Deepali; Bhanage, Avani; Ugle, S. S.; Gurav, Arundhati; Shinde, Ekta (Innovational: Journal of Nursing and Healthcare, 2024)
Aim and Objectives: The aim of this study was to study the effectiveness of administration of pomegranate arils on elevation of hemoglobin level among adolescent girls staying in selected hostel. The objectives are as follows: Assessment of hemoglobin level before administration of pomegranate arils. (1) Assessment of hemoglobin level after administration of pomegranate arils. (2) To evaluate the effectiveness of administration of pomegranate arils on elevation of hemoglobin level among adolescent girls. (3) To find out an association between preintervention and post-intervention hemoglobin level with selected demographic variables. Methods: Quasi experimental one group pre-test and post-test research design was used. Before the collection of data researcher was obtained permission from competent authority of the selected hostel and informed assent/consent was taken from the parent and participants. A total 100 samples were selected as per inclusion criteria; those are hemoglobin less than and near to 12 g/dl. Pre-test was conducted to assess the hemoglobin level of adolescent girls using biochemical assessment – Sahli’s method on day “1.” On the next day, deworming done, next day morning administration of pomegranate arils of 100 g for a period of 30 days to adolescent girls. After, 30 days post-test, hemoglobin estimation was done. Result: The before administration of pomegranate arils mean score was 10.41 and after administration of pomegranate arils mean score was 11.02. The calculated value is 28.3 at 99° of freedom which is higher than the tabulated value that is 1.66 at 5% level of significance. Hence, it was statistically interpreted that (H0 ) null hypothesis was rejected and H1 accepted which state that the pomegranate arils were effective on elevation of hemoglobin level of adolescent girls. Conclusion: The researcher tries to improve hemoglobin level among adolescent girls by administering pomegranate arils 100 g up to 30 days.